Automation of Production by Complexes of Equipment Efficiency Upgrading - Vyacheslav V. TRUTNEV; Mansur F. SAFARGALIEV; Alexander P. SNEGURENKO; Radmir A. GALYAMOV (Communications of International Proceedings, 2021)
The article discusses the main functionality of the hardware and software complex for monitoring the operation of numerically controlled machines, universal equipment, production lines of machine-building production. The principle of receiving data from equipment is based on work with transmitted discrete signals. The results of the production processes implementation in an enterprise subdivision connected to a monitoring system of industrial equipment which is based on automatically generated data and actions of a machine operator are investigated. The minimum generated data is information about processing, shutdown or equipment failure. The data on various states of the enterprise equipment operation, obtained from the reports generated in the monitoring system, are analyzed. Formation of reports is based on tabular and graphical forms of data presentation with various degree of detalization. Identified production losses arising during the operation of industrial equipment on the basis of a subjective assessment of the monitoring system. Production losses are classified according to equipment-specific parameters and according to the classification applied in the lean concept. Organizational and technical recommendations for reducing and eliminating production losses are presented. The depth of recommendations' formation is determined by the level of technological preparation of production, where the maximum level refers to a high-quality organized system.
Keywords: Enterprise Automation; Production Planning; Production Monitoring.